Is there an association between frequency of home mathematical activities (HMA) and children’s mathematical outcomes? Data harmonization and secondary analyses of U.K.-based data sets - Hunt, Benjamin W.; Cahoon, Abbie; Blakey, Emma; James-Brabham, Ella; Matthews, Danielle; Simms, Victoria (Developmental psychology)
Early mathematical skills lay an important foundation for later academic success. Substantial variation in mathematical skills can be observed in young children, and these differences have been related to family socioeconomic circumstances (SEC). The type and frequency with which parents engage in home mathematical activities (HMAs) with their children have been suggested as a key mechanism explaining inequalities in early mathematical skills; they may also be a potential target to narrow attainment gaps. However, evidence for the relation between HMAs and mathematical skills, and whether there is an SEC gradient in HMA engagement, remains mixed. In the present preregistered study, we conducted harmonization and latent profile analyses on nine U.K.-based data sets, containing = 969 dyads: mean child age = 46.83 ( = 5.41) months; child age range = 35-69 months. These analyses identified three profiles based on the frequency of engaging in HMAs (i.e., low, intermediate, high). Children in the high HMA category had significantly higher mathematical skills than those in the intermediate and low categories. While SEC correlated with mathematical skills, no SEC differences were found in engagement with HMAs. This suggests that families that engage in a higher frequency of HMAs have children that tend to have higher mathematical skills, but SEC does not predict engagement with HMAs. We discuss the implications of these findings for narrowing early attainment gaps and how to best measure and capture the home mathematical learning environment. (PsycInfo Database Record (c) 2025 APA, all rights reserved).